Postpartum Estrous Cyclicity and Fertility in Cross - Pokharel, Aashirbad; Gautam, Gokarna (Journal of Nepal Agricultural Research Council, 2025)
This study determined the effect of various factors on the resumption of postpartum (pp) estrous cyclicity within 60 days (d) pp and 90 d pp and pregnancy within 90 d pp in cross-bred dairy cows. Blood was sampled (n=46) once during 50-60 d pp to determine serum glucose, total protein, albumin, urea, blood urea nitrogen and creatinine concentration. Body condition score (BCS) was determined twice- during 50-60 and 80-90 d pp. A total of 16 (34.8%) cows resumed estrous cyclicity within 60 days, and 30 (65.2%) cows resumed estrous cyclicity cumulatively within 90 days postpartum. More cows with BCS>2.50 as compared to cows with BCS≤2.50 during 50-60 d pp resumed estrus within 60 d pp (P<0.05). More cows without periparturient problems-initiated estrus within 60 d pp as compared to cows with periparturient problems (P<0.05). BCS change (from 50-60 to 80-90 d pp) and periparturient problems significantly influenced estrus resumption within 90 d pp (P<0.05). However, breed, parity and milk yield had no influence on the resumption of estrus cyclicity either within 60 d pp or 90 d pp. Among various blood nutritional metabolic parameters, only the serum albumin influenced estrus resumption within 60 d pp (P<0.05). Pregnancy within 90 d pp was significantly influenced by BCS, BCS change and periparturient problems (P<0.05). In conclusion, the resumption of estrous cyclicity postpartum was affected by the periparturient problems, BCS, BCS change and serum albumin level, whereas the pregnancy within 90 d pp was affected by the periparturient problems, BCS and BCS change.